2001
DOI: 10.1007/s002130100887
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of voluntary ethanol intake by cannabinoid receptor agonists in ethanol-preferring sP rats

Abstract: Administration of WIN 55,212-2 and CP 55,940 promoted voluntary ethanol intake in sP rats. This effect was mediated by stimulation of the cannabinoid CB1 receptor and required the activation of the endogenous opioid system. The results of the present study add further support to the hypothesis that the cannabinoid CB1 receptor is part of the neural substrate regulating ethanol intake. These results are also discussed in terms of WIN 55,212-2 and CP 55,940 administration possibly fixing to a higher level the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
109
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(123 citation statements)
references
References 18 publications
12
109
1
1
Order By: Relevance
“…This is in line with the very well characterised stimulatory effects on food intake following CB1 receptor activation (Williams et al 1998;Gomez et al 2002). Previous reports showed that administration of direct cannabinoid receptor agonists like CP 55,940 and WIN 55,212-2 increases alcohol intake and alcohol reinforcement in both nonselected and genetically selected alcoholpreferring rats (Colombo et al 2002;Gallate et al 1999). These effects are mediated by activation of CB1 receptors because they are abolished by pre-treatment with the selective CB1 receptor antagonist rimonabant.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This is in line with the very well characterised stimulatory effects on food intake following CB1 receptor activation (Williams et al 1998;Gomez et al 2002). Previous reports showed that administration of direct cannabinoid receptor agonists like CP 55,940 and WIN 55,212-2 increases alcohol intake and alcohol reinforcement in both nonselected and genetically selected alcoholpreferring rats (Colombo et al 2002;Gallate et al 1999). These effects are mediated by activation of CB1 receptors because they are abolished by pre-treatment with the selective CB1 receptor antagonist rimonabant.…”
Section: Discussionsupporting
confidence: 85%
“…We speculate that drugs like URB597 or other endocannabinoid modulators may offer important advantages over drugs that activate CB1 receptors directly. For instance, CB1 receptor direct agonists show intrinsic abuse potential and increase consumption of other drugs of abuse (Colombo et al 2002;Gallate et al 1999;McGregor et al 2005). Conversely, as shown here, modulation of endogenous anandamide levels did not increase alcohol abuse-related behaviours.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Pharmacological blockade or genetic ablation of CB1 receptors decrease operant self-administration of ethanol (148,149) and decrease voluntary consumption of ethanol in rats (150)(151)(152)(153)(154) and in mice (155)(156)(157)(158)(159). Conversely, cannabinoid CB1 receptor agonists increase voluntary consumption of ethanol in rats (160,161). A caveat for the results obtained with oral self-administration or voluntary consumption of ethanol is that cannabinoid CB1 agonists have facilitating effects and cannabinoid CB1 antagonists have inhibitory effects on food and fluid intake, on the motivation to respond to obtain food, and on ingestive behaviour and palatability (162)(163)(164)(165), and these actions may contribute to the behavioral effects of CB1 receptor blockade or deletion on ethanol selfadministration and voluntary ethanol consumption.…”
Section: Alcoholmentioning
confidence: 99%
“…Interestingly, the prefrontal cortex (PFC) appears to play a critical role in regulating the alcohol drinking behavior as revealed by a dose dependent suppression of alcohol self-administration in alcohol preferring rats when rimonabant was given locally into the PFC [82]. Conversely, the CB1 receptor stimulation is shown to enhance alcohol drinking behavior in both alcohol preferring and alcohol non-preferring rodents [55,61,84,104]. In addition, an increased motivation to drink more beer in rats following administration of the CB1 receptor agonist (CP-55, 940) and complete abolition of this effect after treatment with rimonabant has also been shown [83].…”
Section: Alcoholism and Endocannabinoid Systemmentioning
confidence: 99%